A case of stuttering treated successfully with Aversive Noise Technique - Mahananda P (Journal of All India Institute of Speech and Hearing, 1970)
Mr B., a 19 year old boy, reported to the Institute with a complaint of stuttering. He was studying for his bachelor's degree in education.   He could not give precise information on the time of onset of his problem.   However, he felt that he pro- bably started having problems with his speech when he was about 8 years old. His difficulty had remained almost the same over these years